Transformasi Cerita Rakyat ke Multimedia Interaktif: Inovasi Digital sebagai Bahan Ajar - Setiartin, Titin; Hidayat, Eka Wahyu; Mustofa, Romy Faisal; Putra, Adita Widara (UNIB Press, 2024)
The objective of this research is to transform folklore texts into interactive digital multimedia as teaching materials within a blended learning framework. The digitization of interactive multimedia aims to facilitate students' appreciation of folklore by providing a more engaging learning experience. This study employs a qualitative descriptive method with a mixed qualitative-quantitative approach, following a sequential exploratory design. The stages of designing the interactive multimedia application include actor identification, use case identification, application scenario development, use case diagram design, sequence diagram creation, storyboarding, and navigation structure planning.The final outcome of this research is the development of Action Scripts in a programming language, which can be incorporated into flash files (frames, movie clips, or buttons), resulting in an interactive multimedia application. The application was evaluated using the System Usability Scale (SUS) method, yielding an average SUS score of 77.84. According to the SUS evaluation, the folklore- based interactive multimedia learning application falls within the